(untitled) (Fiep Bulletin - online, 2013)
This study aims to evaluate the motor abilities and relate them with the BMI of male children between the ages of 7 to 11 years old registered on salon football school of Parobé city, Rio Grande do Sul, Brazil. The research took place at the municipal gymnasium of sports, and had a descriptive cross sectional approach. Ninety six male students were part of this research. This sample was stratified by gender and age bracket. The tool used was the Motor Development Scale from Rosa Neto (2002). This study was accomplished with children attending the gymnasium at different time than classes. After getting the Free and Cleared Term of Consent the research took place. Through this research it was concluded that the total of children that are with medium BMI, about 18 and 19 belonging to the group of 9 years old classified according to the WHS table, classified by the Motor Development Scale MDS (ROSA NETO, 2002) as 60.42% regular medium, 38.54% regular high and 1.04% superior, which means, even overweight and obese children reached a good level of motor development. The laterality obtained was 67.70% for right handed, 21.90% for left handed and 10.4% for cross laterality, prevailing the right handed dominance. The results of this study have shown precocity on the motor age of these children.